UNVEILING THE LABYRINTH OF INTERNET PHRASEOLOGY: NAVIGATING THE LINGUISTIC LANDSCAPE OF THE DIGITAL ERA - Navruza Alieva Khabibullaevna; Otakhonova Nurjakhon Ilkhomjon kizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Internet phraseology, the unique language used in online communication, has become an essential aspect of the digital era. This article provides a comprehensive exploration of Internet phraseology, unveiling its evolution, linguistic characteristics, and sociocultural implications. Drawing upon existing research and scholarly contributions, the literature review highlights the role of Internet phraseology in enhancing communication efficiency, its cultural significance in identity construction, and its impact on language innovation and cross-cultural dynamics. The discussion section delves deeper into the implications of Internet phraseology, emphasizing the importance of digital literacy and understanding in navigating its linguistic labyrinth. By embracing Internet phraseology and its dynamic nature, individuals can effectively engage in online communication, bridge cultural divides, and navigate the linguistic landscape of the digital era with confidence and understanding.